MÉTODOS DE EDUCACIÓN INCLUSIVA DE PERSONAS CON DISCAPACIDAD COMO ESTRATEGIA ADECUADA DE RESPONSABILIDAD SOCIAL INTERNA DE LA EMPRESA. - Aparicio Aldana, Rebeca Karina (Revista de Derecho, 2019)
This paper intends to give an account of the duty that affects every business to assume a policy of corporate social responsibility aimed at the inclusion of persons with disabilities; one of the tools most suitable for this purpose being the incorporation of certain methodologies of inclusive education.
Keywords: Coexistenciality; labour relations; inclusive education; disability; business; Employment Law; corporate social responsibility